HUBUNGAN DUKUNGAN KELUARGA DENGAN KESIAPAN REMAJA PUTRI DALAM MENGHADAPI MENARCHE DI SMP NEGERI 1 KAWANGKOAN - Salangka, Gladys; Rompas, Sefti; Regar, Maria (Universitas Sam Ratulangi, 2018)
Abstract : Menarche (first menstruation) is the first menstruation occurred in the uterine wall and is known as menstrual blood. Teenagers who are lack support from parents which is support information, an emotional, appreciation, and instrumental regarding menstruation so teenagers can be prepared to face the arrival of menarche. The purpose of this research was to know the relationship families support with young women facing menarche readiness at 1 Junior High School in Kawangkoa. Research Method: This research was using descriptive analytic survey method with cross sectional time approach. Sample total sampling technique was used as sampling technique for 32 female students who are not yet having menstruation experiences. Result: Based on the Chi-Square test, it showed the significant correlation between two variables with p-value= 0,001 lower than Î±= 0,05 and 0,544 correlation contingency. Conclussion of the this research is there is a Relations Of Families Support In Woman Preparation To Face Menarche In SMP Negeri 1 Kawangkoan. Keywords : Families Support , Preparedness for Menarche. Abstrak : Menarche (Haid pertama) merupakan haid yang pertama kali terjadi pada dinding rahim dan yang dikenal dengan istilah darah haid. Remaja putri perlu mendapatkan dukungan dari orang tua yaitu dukungan informasi, emosional, penghargaan, dan instrumental mengenai menstruasi agar remaja putri memiliki kesiapan yang baik dalam menghadapi datangnya menarche. Tujuan penelitian ini untuk mengetahui hubungan dukungan keuarga dengan kesiapan remaja putri dalam menghadapi menarche. Metode Penelitian mengguanakan metode deskriptif analitik dengan pendekatan cross sectional study. Sampel menggunakan metode pengambilan total sampling yaitu 32 siswi yang belum mengalami menarche. Hasil Penelitian berdasarkan uji Chi-Square menunjukan hasil adanya hubungan antara kedua variabel dengan nilai p=0,001 kurang dari Î±=0,05 dengan korelasi kuat (0,544). Simpulan dari penelitian ini adalah ada hubungan antara dukungan keluarga dengan kesiapan remaja putri dalam menghadapi Menarche di SMP Negeri 1 Kawangkoan. Kata kunci : Dukungan Keluarga, Kesiapan Menghadapi Menarche